LEARNING WITH WORKED-OUT PROBLEMS: THE IMPACTS OF INSTRUCTIONAL EXPLANATION AND SELF-EXPLANATION PROMPTS ON TRANSFER PERFORMANCE - Sern, Lai Chee (Journal of Technical Education and Training, 2010)
In the present research, two different explanatory approaches – namely, instructional explanation and self-explanation prompts – were applied in worked-out-problembased learning (or learning from worked-out problems) in the domain of manufacturing technology. The main purpose of this investigation was to compare the effects of both explanatory approaches on topic knowledge acquisition, near-transfer performance, and far-transfer performance. Additionally, the mental efforts invested by the participants during the learning process were also recorded to examine its relation with learning performance. A pre- and post-tests were used to assess topic knowledge acquisition, near- and far-transfer performance, whereas mental effort was measured by means of NASA Task Load Index. The analysis outcomes revealed that the self-explanation prompts approach was significantly superior to the instructional-explanation approach in terms of topic knowledge acquisition and neartransfer performance. There was no significant difference found between both approaches in far transfer performance. Apart from the above, the findings also demonstrated that a high mental effort investment did not guarantee a fruitful learning performance.